The transformations in the agricultural reality and the rural schools of the regional nucleus of education of Dois Vizinhos - PR - Leandro Turmena; Marcos Vinicius Pereira Ribeiro; Sidemar Presotto Nunes (Universidade Federal do Norte do Tocantins, 2023)
The "country schools", in the state of Paraná, is an educational proposal that, in addition to guaranteeing quality education, considers the specificities of the rural reality. The Regional Education Nucleus of Dois Vizinhos (NRE-DV) is responsible for seven municipalities and serves, in total, fifteen Rural Schools, elementary school (final years) and high school. The research was developed by consulting historical series of the Agricultural Census of the Brazilian Institute of Geography and Statistics (IBGE) and the NRE-DV, in addition to an interview with the manager teacher of the rural schools of the referred Nucleus. The situation of rural schools is linked to the agrarian question, that is, to the set of problems inherent to the development of capitalism in the countryside. Thus, the article analyzes the decrease in the number of enrollments in Rural Schools in recent years, a movement that has occurred due to the decrease in the population residing in rural areas, the concentration of land and changes in agriculture.